2012
DOI: 10.5581/1516-8484.20120071
|View full text |Cite
|
Sign up to set email alerts
|

Antibody responses to Hepatitis B and measles-mumps-rubella vaccines in children who received chemotherapy for acute lymphoblastic leukemia

Abstract: Objective To evaluate viral vaccine antibody levels in children with acute lymphoblastic leukemia after chemotherapy and after vaccine booster doses. Methods Antibody levels against hepatitis B, rubella, measles and mumps vaccine antigens were evaluated in 33 children after completing chemotherapy (before and after vaccine booster doses) and the results were compared to the data of 33 healthy children matched for gender, age and social class. Results After chemotherapy, 75.9%, 67.9%, 59.3% and 51.7% of the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In this issue Viana et al ( 1 ) discuss immunity after chemotherapy for acute lymphoblastic leukemia whose recostitution does not garantee protection against vaccine preventable disease. Current treatment for acute lymphoblastic leukaemia (ALL) cures the majority of patients but as a consequence it causes severe immunosuppression which may even last after completing chemotherapy.…”
mentioning
confidence: 99%
“…In this issue Viana et al ( 1 ) discuss immunity after chemotherapy for acute lymphoblastic leukemia whose recostitution does not garantee protection against vaccine preventable disease. Current treatment for acute lymphoblastic leukaemia (ALL) cures the majority of patients but as a consequence it causes severe immunosuppression which may even last after completing chemotherapy.…”
mentioning
confidence: 99%
“…9 However, other studies have also shown no effect of age on posttreatment vaccine titers in children with ALL. 16,17 While these studies and ours showed that some trends do exist, what is important is that considerable portions of individuals exhibit loss of immunogenicity against VPDs following chemotherapy in all ages throughout these studies.…”
Section: Loss Of Vaccine Response Is Significant and Variable After Cmentioning
confidence: 58%
“…Previous studies demonstrate intensive chemotherapy may cause notable decreases in vaccine-specific antibody titers in childhood cancer survivors (CCS). [1][2][3][4][5][6] In CCS, the loss of protective antibodies poses a risk from vaccine-preventable infections well after immune reconstitution. 7 These potentially life-threatening infections represent an avoidable source of morbidity and mortality and may create potential disease vectors that threaten public health initiatives.…”
Section: Introductionmentioning
confidence: 99%